Characterisation of Newcastle Disease Virus (NDV) Isolates and Development of Real-Time PCR for Diagnosis of NDV - Tan, Sheau Wei (2003)
A sudden upsurge of Newcastle disease (ND) outbreaks occurred in Malaysia with high mortality among vaccinated birds started in August 2000 and peaked between November 2000 and March 2001. Four isolates; 00/IKS, 0l/C, 01/TM and Ol/GNS were isolated from the NDV outbreaks in different states in Peninsular Malaysia. Mean death time (MDT) assay was carried out to determine the pathogenicity of the isolates in embryonated chicken eggs. All isolates had MDT of less than 60 hours, indicating that the isolates are velogenic. The nucleotide sequence in the region of F cleavage site for the four NDV isolates were determined and the deduced amino acid sequence showed that all isolates possessed two pairs of basic amino acids (112RRQKR116) and Phe residue at position 117 of the F cleavage site. These amino acid sequences correlated with the MDT results which confirmed that the four NOV isolates are velogenic strains. Analysis of the partial sequence of the F gene was carried out and the results suggested that the four recent isolates can be grouped under the genotype VII viruses. All the isolates possess K101 and V121 at the F gene sequence, a characteristic of genotype VII viruses. Isolates 0l/C had an N residue at position 101, which is unique among these four isolates. The phylogenetic analysis of the four isolates based on the partial sequence of M gene showed that their nucleotide similarities varied between 92.7% and 100%, where isolate 00/IKS shared 100% nucleotide sequence similarity with isolate Ol/GNS. The four isolates were found to be phylogenetic ally related to pigeon isolate 1307/US/75 and goose isolate ZJI with similarity ranging from 93.29% to 98.38%. This suggests that the recent isolates might have originated from domestic and free-living birds. There was no evidence to show that the recent isolates evolved from local velogenic NDY strain AF2240, which was isolated in 1960s. The nucleotide similarities of the four NDY isolates with strain AF2240 were 79.88% to 82.63%. Recent development of real-time PCR has offered the opportunity of developing a sensitive and accurate method to detect NDY. A two-step real-time RT-PCR procedure using the SYBR Green I dye was used as a detection signal. Beside the four isolates, 8 other isolates of NDV were used in this study. They were grouped into 7 velogenic, 1 meso genic and 4 lentogenic strains. All isolates showed positive results in amplification. A melting curve was obtained immediately after amplification to distinguish specific product from non-specific and primer-dimer. From the melting curve analysis, no primer-dimer and non-specific products were detected and all the isolates had melting temperature (Tm) ranging from 86°C to 87°C. The detection limits of the real-time PCR were compared with R T -nested PCR ELISA and agarose gel electrophoresis by preparing serially ten-fold dilutions of the cDNA. The real-time PCR could detect up to 1:10^5 dilution of cDNA with the concentration of 1.1 x 10-5 ug/ul. However, ELISA assay detection limit reached 1:103 with the concentration of 1.1 x10-3 ug/ul, whereas the agarose gel electrophoresis can only detect up to 1:10^2 dilution of the cDNA (1.1 x 10-2 ug/ul) with a faint band. The SYBR Green I real-time peR was found to be 100-fold more sensitive thari the peR-ELISA detection method. The study has therefore successfully developed a sensitive, rapid and convenient method for NDV diagnosis using real-time peR with SYBR Green I as a detection signal.